Observation of surface species in plasma-catalytic dry reforming of methane in a novel atmospheric pressure dielectric barrier discharge in situ IR cell. Issue 22 (10th October 2022) - Van Turnhout, Joran; Aceto, Domenico; Travert, Arnaud; Bazin, Philippe; Thibault-Starzyk, Frédéric; Bogaerts, Annemie; Azzolina-Jury, Federico
Abstract : Our in situ operando IR DBD cell makes it possible to study the surface species formed in a plasma-catalytic system. Abstract : We developed a novel in situ ( i.e. inside plasma and during operation) IR dielectric barrier discharge cell allowing investigation of plasma catalysis in transmission mode, atmospheric pressure, flow conditions (WHSV ∼0–50 000 mL g −1 h −1 ), at relevant discharge voltages (∼0–50 kV) and frequencies (∼0–5 kHz). We applied it to study the IR-active surface species formed on a SiO2 support and on a 3 wt% Ru/SiO2 catalyst, which can help to reveal the important surface reaction mechanisms during the plasma-catalytic dry reforming of methane (DRM). Moreover, we present a technique for the challenging task of estimating the temperature of a catalyst sample in a plasma-catalytic system in situ and during plasma operation. We found that during the reaction, water is immediately formed at the SiO2 surface, and physisorbed formic acid is formed with a delay. As Ru/SiO2 is subject to greater plasma-induced heating than SiO2 (with a surface temperature increase in the range of 70–120 °C, with peaks up to 150 °C), we observe lower amounts of physisorbed water on Ru/SiO2, and less physisorbed formic acid formation. Importantly, the formation of surface species on the catalyst sample in our plasma-catalytic setup, as well as the observed conversions and selectivities in plasma conditions, can not be explained by plasma-induced heating of the catalyst surface, but must be attributed to other plasma effects, such as the adsorption of plasma-generated radicals and molecules, or the occurrence of Eley–Rideal reactions.